Durable Solutions Bagi Pengungsi Etnis Rohingya Tanpa Kewarganegaraan Menurut Hukum Internasional - Ranty, Aprianti; Lestari, Maria Maya; Deliana, Evi (Fakultas Hukum Universitas Pattimura, 2024)
Introduction: The ethnic Rohingya are an ethnic Muslim minority group in Rakhine, which is among the most persecuted, vulnerable, and oppressed minorities in the world. In addition to losing their citizenship, the ethnic Rohingya also lost their home, where they have lived for decades. The United Nations High Commissioners for Refugees or UNHCR is an international organization that deals specifically with refugees. With the function of providing protection and finding long-term solutions for refugees.Purposes of the Research: Analyze Durable Solutions that are suitable to be applied to Stateless Rohingya ethnicity.Methods of the Research: The type of research that will be used is normative law research, which focuses on positive legal norms such as international law instruments relating to the issues contained in this study.Results of the Research: Of the three durable solutions available to UNHCR, the most viable long-term solution for Rohingya refugees is resettlement or relocation to a third country. Because of the conditions and laws relating to the citizenship of Bangladesh as a state of asylum, Rohingya refugees do not allow local integration into the nationality of Bangladesh, while voluntary repatriation is not possible for Rohingyas because of the state of the government of Myanmar and the lack of security and security guarantees as well as citizens' rights for rohingya. The protection and realization of the rights of refugees is the responsibility of UNHCR as an international organization formed and under the auspices of the United Nations (United Nations) specifically designed to deal with the refugee problem under the Statute of the Office of the High Commissioner for Refugees 1951 or the 1951 Convention. But UNHCR's authority is limited to providing protection, assistance, fulfilling the rights of refugees, and seeking solutions. This limitation of authority is what makes it difficult for UNHCR to carry out its tasks and missions.